2006
DOI: 10.1002/chin.200642267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Reactions Used for the Preparation of Drug Candidate Molecules

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 1 publication
3
106
1
1
Order By: Relevance
“…In combination with the imidazolium salt 35b (see Table 1), sodium hydride and acetonitrile, this complex readily converted a variety of aliphatic and aromatic aldehydes into amides (Scheme 30). Further studies on the stoichiometric reactivity of [RuH 2 (PPh 3 ) 4 ] with NaH at 110ºC suggested the formation of ruthenium(0) species during the catalytic events. This proposal was also supported by fact that the ruthenium(0) complexes [Ru 3 (CO) 12 ] and [Ru(cod)(cot)], associated with 35b and NaH, proved to be also active in the process.…”
Section: Starting From Aldehydesmentioning
confidence: 99%
See 3 more Smart Citations
“…In combination with the imidazolium salt 35b (see Table 1), sodium hydride and acetonitrile, this complex readily converted a variety of aliphatic and aromatic aldehydes into amides (Scheme 30). Further studies on the stoichiometric reactivity of [RuH 2 (PPh 3 ) 4 ] with NaH at 110ºC suggested the formation of ruthenium(0) species during the catalytic events. This proposal was also supported by fact that the ruthenium(0) complexes [Ru 3 (CO) 12 ] and [Ru(cod)(cot)], associated with 35b and NaH, proved to be also active in the process.…”
Section: Starting From Aldehydesmentioning
confidence: 99%
“…In this context, ruthenium complexes are among the most versatile nitrile hydration catalysts discovered with regard to activity, selectivity and tolerance to functional groups. 4 ] upon treatment with 1-2 equivalents of water in DME at 120 ºC, leading to the corresponding primary amides in high yields (TOF up to 2 h -1 ). A catalytic cycle involving the initial coordination of the nitrile to ruthenium, followed by intermolecular nucleophilic attack of water to generate an iminol that tautomerizes into the amide, was proposed (Scheme 2) [24].…”
Section: Ruthenium-catalyzed Hydration Of Nitrilesmentioning
confidence: 99%
See 2 more Smart Citations
“…and often is used for the production of chiral drugs 74 or drug intermediates as one of the preferred methods for the generation of chirality, 75 especially if the chirality should be introduced during one of the early stages of the drug synthesis sequence. 76 The reason for this choice is the high availability of screening methods and the increased understanding of crystallization during the scale-up process.…”
Section: The Main Strategies To Access Optically Active Productsmentioning
confidence: 99%